Identifying the Misconceptions of Natural Science (IPA) Using CRI (Certanty of Response Index) at the Primary School Students in Tarakan - Muhsinah Annisa; Ratna Yulinda; Kartini Kartini (JIPF (Jurnal Ilmu Pendidikan Fisika), 2017)
The objective of this study is to identify the misconceptions of Natural Science (IPA) on primary school students in Tarakan. The output of this study is presented into a national scientific journal with ISSN. This study absolutely contributes to the schools and the education providers (universities). This study can identify the misconceptions of what happens to the students, so that teachers know how to handle and remediate these misconceptions. This study employs quantitative descriptive research. The population is the sixth grade students of primary schools in Tarakan. It is because the students of this grade have got the learning material on force, light, and simple machine. The technique.;s used in taking the sample is cluster sampling by considering on the three criteria, namely: superior, medium, and low school category which is based on the mean scores of final test (UAS) on natural science subject. So, the sixth grade students of SDN A, SDN B Tarakan, and SDN C Tarakan are chosen as the sample of this study. The instrument of this research is a written test in a form of multiple choice test equiped with the CRI (certainty of response index) answer sheet. The data are collected by distributing multiple-choice test which is consisted of 40 questions that are equipped with the CRI answer sheet.